Solid electrolyte and solid electrolyte joint
Apatite-type composite oxides with specific X-ray diffraction peak ratios and metal oxide layers lower interfacial resistance, enhancing the conductivity and performance of devices with solid electrolytes.
Patent Information
- Application Number
- JP2023110730
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-06-08
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2039-05-31
AI Technical Summary
Existing solid electrolytes with high oxide ion conductivity face high electrical resistance at the interface with electrodes, limiting the performance of devices that utilize them.
Employing an apatite-type composite oxide with a specific crystal structure and a peak intensity ratio of 004 to 002 X-ray diffraction peaks between 0.3 and 0.8, and incorporating a metal oxide intermediate layer or metal electrode layer to reduce interfacial resistance.
The solution significantly reduces the electrical resistance of the device, enhancing oxide ion conductivity and improving the overall performance of devices using solid electrolytes.
Smart Images

Figure 0007617982000003 
Figure 0007617982000004 
Figure 0007617982000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid electrolyte and a solid electrolyte joint. The solid electrolyte and the solid electrolyte joint of the present invention are used in various fields making use of their oxide ion conductivity. [Background technology]
[0002] Various oxide ion conductive solid electrolytes are known. Such solid electrolytes are used in various fields, for example, as oxygen permeable elements, electrolytes for fuel cells, and gas sensors. For example, Patent Document 1 describes an electrolyte-electrode assembly in which a solid electrolyte made of an apatite-type composite oxide is interposed between an anode electrode and a cathode electrode. An intermediate layer exhibiting isotropic oxide ion conduction is interposed between the cathode electrode and the solid electrolyte. The intermediate layer is made of cerium oxide doped with samarium, yttrium, gadolinium, or lanthanum. The solid electrolyte is made of La x SiO 1.5X+12 (8≦X≦10). The document states that this electrolyte-electrode assembly improves the power generation performance of solid oxide fuel cells. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2013-51101 A Summary of the Invention
[0004] As described in Patent Document 1, various devices using oxide-ion conductive solid electrolytes have been proposed, but when evaluated as a whole device, it cannot be said that the oxide-ion conductivity inherent to the solid electrolyte is fully utilized. In particular, even if the oxide-ion conductivity of the solid electrolyte itself is high, the electrical resistance at the interface between the solid electrolyte and the electrode may become high, and the electrical resistance of the whole device may become high.
[0005] Therefore, an object of the present invention is to provide a solid electrolyte capable of reducing the electrical resistance of a device including a solid electrolyte, and a solid electrolyte junction including the solid electrolyte.
[0006] As a result of intensive research by the present inventors to solve the above problems, it was found that the above problems can be solved by using an apatite-type composite oxide having a specific crystal structure as a solid electrolyte. The present invention was made based on this finding, and provides a solid electrolyte comprising an apatite-type composite oxide having oxide ion conductivity, and having a peak intensity I of 004 obtained by X-ray diffraction measurement. 004 Peak intensity of 002 against I 002 The ratio of I 002 / I 004 The above-mentioned problems have been solved by providing a solid electrolyte in which the value of is 0.3 or more and 0.8 or less.
[0007] The present invention also provides a solid electrolyte joint comprising the above solid electrolyte joined to an intermediate layer of a metal oxide or a metal electrode layer. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic diagram showing one embodiment of a device including a solid electrolyte of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing another embodiment of a device including a solid electrolyte of the present invention. [Diagram 3] FIG. 3 is a schematic diagram showing still another embodiment of a device including a solid electrolyte of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described below based on preferred embodiments thereof. The solid electrolyte of the present invention is made of an apatite-type composite oxide having oxide ion conductivity. The solid electrolyte is a conductor in which oxide ions serve as carriers.
[0010] An example of an apatite-type composite oxide is a composite oxide containing lanthanum and silicon. This apatite-type composite oxide contains lanthanum (La), a trivalent element, silicon (Si), and oxygen (O), and has a composition of La. x SiO 1.5x+12 (x is a number of 8 or more and 10 or less) is preferred from the viewpoint of high oxide ion conductivity. The most preferred composition of this apatite-type composite oxide is La 9.33 SiO 26 This composite oxide can be produced, for example, according to the method described in JP 2013-51101 A.
[0011] Another example of an apatite-type composite oxide is a compound represented by the general formula (1): A 9.33+x [T 6.00-y M y ]O 26.0+z Examples of the composite oxide include a composite oxide represented by the formula: This composite oxide also has an apatite structure. In the formula, A is one or more elements selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Be, Mg, Ca, Sr and Ba. In the formula, T is an element containing Si or Ge or both. In the formula, M is one or more elements selected from the group consisting of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Ga, Zr, Ta, Nb, B, Ge, Zn, Sn, W and Mo. From the viewpoint of increasing the c-axis orientation, M is preferably one or more elements selected from the group consisting of B, Ge and Zn.
[0012] In the formula, x is preferably -1.33 to 1.50, more preferably 0.00 to 0.70, and even more preferably 0.45 to 0.65, from the viewpoint of increasing the degree of orientation and oxide ion conductivity. In the formula, y is preferably 0.00 to 3.00, more preferably 0.40 to 2.00, and even more preferably 0.40 to 1.00, from the viewpoint of filling the T element position in the apatite type crystal lattice. In the formula, z is preferably -5.00 to 5.20, more preferably -2.00 to 1.50, and even more preferably -1.00 to 1.00, from the viewpoint of maintaining electrical neutrality in the apatite type crystal lattice.
[0013] In the above formula, the ratio of the number of moles of A to the number of moles of T, in other words, (9.33+x) / (6.00-y) in the above formula, is preferably 1.33 or more and 3.61 or less, more preferably 1.40 or more and 3.00 or less, and even more preferably 1.50 or more and 2.00 or less, from the viewpoint of maintaining the spatial occupancy rate in the apatite-type crystal lattice.
[0014] Among the composite oxides represented by the above general formula (1), the composite oxide in which A is lanthanum, i.e., La 9.33+x [T 6.00-y M y ]O 26.0+z It is preferable to use a composite oxide represented by the formula: La 9.33+x [T 6.00-y M y ]O 26.0+z Specific examples of composite oxides represented by the formula are La 9.33+x (Si 4.70 B 1.30 )O 26.0+z , La 9.33+x (Si 4.70 Ge 1.30 )O 26.0+z , La 9.33+x (Si 4.70 Zinc 1.30 )O 26.0+z , La 9.33+x (Si 4.70 W1.30 )O 26.0+z , La 9.33+x (Si 4.70 Sn 1.30 )O 26.0+x , La 9.33+x (Ge 4.70 B 1.30 )O 26.0+z The composite oxide represented by the general formula (1) can be produced, for example, according to the method described in US2018 / 183068A1.
[0015] In any case where any of the above-mentioned apatite-type complex oxides is used as the apatite-type complex oxide, it is preferable that the complex oxide contains lanthanum, since it can effectively reduce the electrical resistance of the device containing the solid electrolyte of the present invention. In addition, in any case where any of the apatite-type complex oxides is used, it is preferable that the complex oxide is oriented along the c-axis. Oriented along the c-axis means that, when the apatite-type complex oxide is a polycrystalline body, the crystal axis is aligned along the c-axis. Furthermore, when the apatite-type complex oxide exists as a single crystal, it is possible to make the c-axis direction coincide with the conduction direction of oxide ions in the device.
[0016] When the apatite-type composite oxide is subjected to X-ray diffraction measurement, the peak intensity I 004 Peak intensity of 002 against I 002 The ratio of I 002 / I 004One of the characteristics of the present invention is that the value of is 0.3 to 0.8. Up until now, when an apatite-type complex oxide strongly oriented to the c-axis is subjected to X-ray diffraction measurement, the diffraction peak intensity other than 00x (x is an even number of 2 or more) is very small, making quantitative analysis difficult. However, the present inventor has found that the intensity ratio of the diffraction peaks of 002 and 004 strongly reflects the amount of defective sites, and has further found that an apatite-type complex oxide having an intensity ratio within a specific range has a low interfacial resistance with the electrode layer and reduces the electrical resistance of the entire device. In particular, when the apatite-type complex oxide contains lanthanum, if the complex oxide maintains the apatite-type crystal structure while losing lanthanum, oxygen in the structure also loses in order to maintain the balance of electric charge. The present inventor believes that when oxygen deficiency occurs, oxide ions are more likely to move, improving the conductivity of oxide ions, and thus further reducing the interfacial resistance between the complex oxide and the electrode layer. In addition, it is believed that the same mechanism as described above occurs for A other than lanthanum, since it is easy for A to enter the same crystal site as lanthanum in the apatite-type composite oxide. In this way, the present invention aims to increase the oxide ion conductivity not due to the intermediate layer or electrode layer joined to the solid electrolyte, but due to the crystal structure of the solid electrolyte itself.
[0017] The greater the amount of defects in the apatite-type composite oxide, the greater the I 004 I 002 The ratio of I to I becomes smaller, and the interface resistance between the apatite-type composite oxide and the electrode layer becomes lower. 004 I 002 The value of the ratio is preferably 0.5 or more and 0.8 or less, and more preferably 0.5 or more and 0.75 or less.
[0018] I 002 and I 004 The value is measured by X-ray diffraction. In detail, it can be measured by using a point-converging X-ray focusing mirror (CMF optical system) and a zero-dimensional detector. The peak intensity of X-ray diffraction in the present invention means the integrated intensity.
[0019] Regarding the X-ray diffraction peak intensity, in order to more accurately measure the amount of defective sites in the apatite-type crystal structure, the peak intensity ratio of 002 and 004, which gives a higher X-ray diffraction intensity, was selected as an index. Note that the positions of the 002 and 004 X-ray diffraction peaks in the apatite-type crystal structure can be uniquely determined from a known crystal database or the like.
[0020] I 004 I 002 In order to make the ratio satisfy the above-mentioned range, it is preferable to form a deficiency site in the apatite-type complex oxide. As a result of the study by the present inventor, it was found that it is advantageous to form a film of a different composition adjacent to the apatite-type complex oxide and anneal the film to remove constituent elements, particularly lanthanum, from the crystal structure in order to form a deficiency site. In this case, it is necessary to remove constituent elements such as lanthanum while maintaining the apatite-type crystal structure. For this purpose, a film in which lanthanum can be diffused or in which lanthanum can be solid-dissolved (hereinafter also referred to as "La absorbing film") is laminated on the surface of the apatite-type complex oxide. Then, it is preferable to obtain an apatite-type complex oxide in which lanthanum is deficient by annealing at a high temperature of 700°C or more to diffuse or dissolve the lanthanum in the apatite-type complex oxide into the La absorbing film. The La absorbing film may then be removed by a predetermined means.
[0021] The solid electrolyte of the present invention can be used as it is, or can be used in the form of a device in which it is combined with other components, depending on the specific application. An example of such a device is shown in Fig. 1. The device shown in Fig. 1 is a solid electrolyte assembly 10 including the solid electrolyte of the present invention. This solid electrolyte assembly 10 will be described below.
[0022] As shown in Fig. 1, a solid electrolyte joint 10 includes a layer 11 made of the above-mentioned solid electrolyte (hereinafter referred to as "solid electrolyte layer"). An intermediate layer 12 is laminated on and in contact with the solid electrolyte layer 11 and joined to one surface of the solid electrolyte layer 11. In the embodiment shown in Fig. 1, the solid electrolyte layer 11 and the intermediate layer 12 are in direct contact with each other, with no other layer interposed between them. The intermediate layer 12 is made of a material having oxide ion conductivity and electron conductivity.
[0023] The thickness of the solid electrolyte layer 11 is preferably 10 nm or more and 1000 μm or less, more preferably 50 nm or more and 700 μm or less, and even more preferably 100 nm or more and 500 μm or less, from the viewpoint of effectively reducing the electrical resistance of the solid electrolyte assembly 10. The thickness of the solid electrolyte layer 11 can be measured using, for example, a stylus step gauge, a vernier caliper, or an electron microscope.
[0024] As shown in Fig. 1, the solid electrolyte joint 10 may have a metal electrode layer 13 bonded to one of the two surfaces of the solid electrolyte layer 11, the surface opposite to the surface on which the intermediate layer 12 is disposed. The solid electrolyte layer 11, the intermediate layer 12, and the metal electrode layer 13 are disposed in this order to form a device 20 made of the solid electrolyte joint 10. In the embodiment shown in Fig. 1, the solid electrolyte layer 11 and the metal electrode layer 13 are in direct contact with each other, with no other layer interposed between them.
[0025] The intermediate layer 12 is configured to contain a metal oxide. The intermediate layer 12 is composed of only a metal oxide, or contains a metal oxide and other substances. The intermediate layer 12 is formed for the purpose of smoothly transferring oxide ions between the solid electrolyte layer 11. According to this embodiment, since the solid electrolyte having the above-mentioned specific crystal structure is used as the solid electrolyte layer 11, it is possible to reduce the interface resistance between the solid electrolyte layer 11 and the intermediate layer 12 regardless of the type of the intermediate layer 12, and it is possible to more smoothly transfer oxide ions.
[0026] The intermediate layer 12 is preferably made of a metal oxide and has oxide ion conductivity. For example, cerium oxide containing one or more elements selected from the group consisting of samarium, yttrium, gadolinium, and lanthanum (hereinafter, these elements are also referred to as "doping elements" for convenience) can be used as the intermediate layer 12. In this case, the content of the doping element is preferably 0.1 mol% to 0.5 mol%, more preferably 0.15 mol% to 0.4 mol%, and even more preferably 0.2 mol% to 0.3 mol%, expressed as M / (M+Ce)×100 (M represents the number of moles of the doping element).
[0027] An oxide of bismuth can also be used for the intermediate layer 12. Examples of the oxide of bismuth include bismuth (III) oxide and composite oxides of bismuth and other metal elements. Examples of the other metal elements include one or more rare earth elements. Examples of the rare earth elements include lanthanum, gadolinium, yttrium, erbium, ytterbium, and dysprosium. In particular, it is preferable that the intermediate layer 12 contains a composite oxide of bismuth and lanthanum, gadolinium, or yttrium, from the viewpoint of effectively reducing the electrical resistance between the solid electrolyte layer 11 and the intermediate layer 12. Furthermore, the composite oxide is preferably (Ln m Bi n In the formula, Ln represents a rare earth element. The sum of m and n is 1, and n>0. Moreover, m is preferably 0.1 or more and 0.4 or less.
[0028] A mixed conductor having oxide ion conductivity and electronic conductivity can also be used as the intermediate layer 12. A mixed conductor is a material having two conductivities, that is, oxide ion conductivity and electronic conductivity, that is, mixed conductivity. In particular, from the viewpoint of achieving lattice matching of a plane perpendicular to the orientation direction at the interface between the solid electrolyte layer 11 and the intermediate layer 12, it is preferable that the material constituting the intermediate layer 12 is a perovskite type oxide. In particular, when the material constituting the solid electrolyte layer 11 is represented by the above-mentioned general formula (1), the lattice matching can be successfully achieved if the material constituting the intermediate layer 12 is a perovskite type oxide.
[0029] In particular, from the viewpoint of further improving oxide ion conductivity, it is preferable to use a material represented by general formula (2): ABO3 as the material constituting the intermediate layer 12. In the formula, it is preferable to use one or more metal elements selected from La, Sr, Ba, and Ca, for example, and a particularly preferable metal element is at least one of La and Sr. B is a transition metal element, and it is preferable to use one or more metal elements selected from Co, Ni, Mn, Cr, Ti, Fe, and Cu, and a particularly preferable metal element is at least one of Co and Ni. In particular, it is preferable that the material represented by general formula (2) is a composite oxide containing La, Sr, Co, and Ni.
[0030] Among the composite oxides represented by the general formula (2), La 0.6 Sr 0.4 Co 0.9 Ni 0.1 O 3-δ It is expressed as follows.
[0031] The intermediate layer 12 made of the composite oxide represented by the general formula (2) can be formed on one side of the solid electrolyte layer 11 by using, for example, various thin film formation methods. Examples of thin film formation methods include physical vapor deposition and chemical vapor deposition, and among these, the intermediate layer 12 can be formed more successfully by using the physical vapor deposition method. Among the physical vapor deposition methods, it is particularly preferable to use the PLD (Pulsed Laser Deposition) method.
[0032] Regardless of which of the above-mentioned materials is used for the intermediate layer 12, it is effective from the viewpoint of reducing the interface resistance that the material constituting the solid electrolyte layer 11 and the material constituting the intermediate layer 12 are both uniaxially oriented along the stacking direction of the solid electrolyte layer 11 and the intermediate layer 12. In order to uniaxially orient the material constituting the solid electrolyte layer 11 and the material constituting the intermediate layer 12 along the stacking direction, for example, while heating the solid electrolyte layer 11 as the substrate to a predetermined temperature, a physical vapor deposition method or a chemical vapor deposition method may be used in an atmosphere with a controlled oxygen partial pressure to form a thin film of the intermediate layer 12 on the solid electrolyte layer 11, and locally epitaxially grow the thin film. In addition, the uniaxially oriented thin film of the intermediate layer 12 may be formed on the solid electrolyte layer 11 by using atomic layer deposition (ALD). However, the method is not limited to these methods.
[0033] Whether or not the material constituting solid electrolyte layer 11 and the material constituting intermediate layer 12 are both uniaxially oriented can be determined by observing a cross section of the joint interface with a TEM (transmission electron microscope). The lattice constants and interplanar spacings of solid electrolyte layer 11 and intermediate layer 12 can be calculated from a diffraction pattern obtained by performing X-ray diffraction measurement while rocking.
[0034] Regardless of which of the above-mentioned materials is used for intermediate layer 12, intermediate layer 12 can effectively reduce the electrical resistance between solid electrolyte layer 11 as long as it has a predetermined thickness. In particular, the thickness of intermediate layer 12 bonded to solid electrolyte layer 11 in the stacking direction is preferably 80 nm or more, more preferably 100 nm or more, and even more preferably 100 nm or more and 1000 nm or less. The thickness of intermediate layer 12 can be measured by a stylus step gauge or an electron microscope.
[0035] The metal electrode layer 13 formed on the opposite side of the intermediate layer 12 across the solid electrolyte layer 11 is preferably composed of a platinum group element, since it has advantages such as ease of formation and high catalytic activity. Examples of the platinum group elements include platinum, ruthenium, rhodium, palladium, osmium, and iridium. These elements can be used alone or in combination of two or more. The metal electrode layer 13 can also be a cermet containing a platinum group element.
[0036] The solid electrolyte assembly 10 and the device 20 of the embodiment shown in Fig. 1 can be suitably manufactured, for example, by the method described below. First, the solid electrolyte layer 11 is manufactured by a known method. For the manufacture, for example, the methods described in JP2013-51101A and US2018 / 183068A1 can be adopted.
[0037] Next, the intermediate layer 12 is formed on one of the two surfaces of the solid electrolyte layer 11. Various thin film formation methods can be used to form the intermediate layer 12. As one of the thin film formation methods, for example, the PLD method described above can be used. Specifically, in order to uniaxially orient both the material constituting the solid electrolyte layer 11 and the material constituting the intermediate layer 12 along the lamination direction of the solid electrolyte layer 11 and the intermediate layer 12, the solid electrolyte layer 11 may be heated to a predetermined temperature when the intermediate layer 12 is formed on one surface of the solid electrolyte layer 11 using the PLD method described above. The heating temperature is preferably set to, for example, 600° C. or more and 700° C. or less in terms of more successful uniaxial orientation.
[0038] After the intermediate layer 12 is formed in this manner, the metal electrode layer 13 is formed on the surface of the solid electrolyte layer 11 opposite to the surface on which the intermediate layer 12 is formed. For example, a paste containing particles of a platinum group metal is used to form the metal electrode layer 13. The paste is applied to the surface of the solid electrolyte layer 11 to form a coating film, and the coating film is fired to form an electrode made of a porous body. The firing conditions can be a temperature of 600°C or higher and a time of 30 minutes to 120 minutes. The atmosphere can be an oxygen-containing atmosphere such as air.
[0039] The above method provides the desired solid electrolyte assembly 10 and device 20. The device 20 thus obtained is suitable for use as, for example, an oxygen permeable element, various gas sensors including an oxygen sensor, steam electrolysis, or a solid electrolyte fuel cell, taking advantage of its high oxide ion conductivity. Whatever the application of the device 20, it is advantageous to use the intermediate layer 12 as a cathode, that is, as an electrode where a reduction reaction of oxygen gas occurs. For example, when the device 20 is used as an oxygen permeable element, the metal electrode layer 13 is connected to the anode of a DC power source, and the intermediate layer 12 is connected to the cathode of the DC power source, and a predetermined DC voltage is applied between the intermediate layer 12 and the metal electrode layer 13. As a result, oxygen receives electrons on the intermediate layer 12 side, and oxide ions are generated. The generated oxide ions move through the solid electrolyte layer 11 to reach the metal electrode layer 13. The oxide ions that reach the metal electrode layer 13 release electrons and become oxygen gas. This reaction enables solid electrolyte layer 11 to transmit oxygen gas contained in the atmosphere on the intermediate layer 12 side to the metal electrode layer 13 side through solid electrolyte layer 11. If necessary, a current collecting layer made of a conductive material such as platinum may be formed on at least one of the surface of intermediate layer 12 and the surface of metal electrode layer 13.
[0040] From the viewpoint of increasing the amount of oxygen gas permeated, the applied voltage is preferably set to 0.1 V or more and 4.0 V or less. When a voltage is applied between the two electrodes, it is preferable that the oxide ion conductivity of the solid electrolyte layer 11 is sufficiently high. For example, the oxide ion conductivity is 1.0×10 -3 It is preferable that the conductivity of the solid electrolyte layer 11 is at least 300° C. / cm. For this purpose, it is preferable to hold the solid electrolyte layer 11 or the entire device 20 at a predetermined temperature. This holding temperature depends on the material of the solid electrolyte layer 11, but is generally preferably set in the range of 300° C. to 600° C. By using the device 20 under these conditions, oxygen gas contained in the atmosphere on the intermediate layer 12 side can be transmitted through the solid electrolyte layer 11 to the metal electrode layer 13 side.
[0041] When the device 20 is also used as a limiting current type oxygen sensor, a current is generated due to the migration of oxide ions generated on the intermediate layer 12 side to the metal electrode layer 13 side via the solid electrolyte layer 11. Since the current value depends on the oxygen gas concentration on the intermediate layer 12 side, the oxygen gas concentration on the intermediate layer 12 side can be measured by measuring the current value.
[0042] Although the present invention has been described above based on its preferred embodiments, the present invention is not limited to the above embodiments. For example, in the above embodiment, the intermediate layer 12 is disposed on only one surface of the solid electrolyte layer 11. Instead, as shown in FIG. 2, a separate intermediate layer 12' may be disposed on the surface of the solid electrolyte layer 11 facing the intermediate layer 12. When a separate intermediate layer 12' is disposed on the surface of the solid electrolyte layer 11 facing the intermediate layer 12, the intermediate layers 12, 12' may be the same or different. In this case, it is preferable that the material constituting the solid electrolyte layer 11, the material constituting one intermediate layer 12, and the material constituting the other intermediate layer 12' are all uniaxially oriented along the lamination direction.
[0043] 3, metal electrode layers 13, 13' may be formed on each surface of solid electrolyte layer 11 instead of intermediate layers 12, 12'. Even in this case, the electrical resistance of device 20 as a whole can be reduced. Metal electrode layers 13, 13' may be the same or different. EXAMPLES
[0044] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".
[0045] Example 1 La2O3 powder and SiO2 powder were mixed in a molar ratio of 1:1, ethanol was added, and the mixture was mixed in a ball mill. The mixture was dried, crushed in a mortar, and fired in a platinum crucible at 1650°C for 3 hours in an air atmosphere. Ethanol was added to the fired product, and the product was crushed in a ball mill to obtain a fired powder. The fired powder was placed in a 20mmφ molding machine and pressed from one direction to perform uniaxial molding. Further, cold isostatic pressing (CIP) was performed at 700MPa for 1 minute to form a pellet. The pellet-shaped molded body was heated in air at 1600°C for 3 hours to obtain a pellet-shaped sintered body. The sintered body was subjected to powder X-ray diffraction measurement and chemical analysis, and it was confirmed that the structure was La2SiO5 with an apatite-type crystal structure.
[0046] 800 mg of the obtained pellets and 140 mg of B2O3 powder were placed in a sagger with a lid. Using an electric furnace, the pellets and B2O3 powder were heated in the air at 1550°C (furnace atmosphere temperature) for 50 hours. This heating generated B2O3 vapor in the sagger and caused the B2O3 vapor to react with the pellets, obtaining the intended solid electrolyte layer 11. This solid electrolyte layer 11 was composed of La 9.33+x [Si 6.00-y B y ]O 26.0+zIn this case, x=0.50, y=1.17, z=0.16, and the molar ratio of La to Si was 2.04. The thickness measured by a vernier caliper was 350 μm. Hereinafter, this compound is abbreviated as "LSBO."
[0047] [Production of La-absorbing film] The Bi2O3 powder was placed in a 50 mmφ molding machine, pressed from one direction to perform uniaxial molding, and then hot press sintering was performed. The sintering conditions were a nitrogen gas atmosphere, a pressure of 30 MPa, a temperature of 600°C, and 3 hours to obtain a sputtering target. Using this target, sputtering was performed on both sides of the solid electrolyte layer 11 made of LSBO to a thickness of 300 nm by a high-frequency sputtering method. The sputtering conditions were an RF output of 30 W and an argon gas pressure of 0.8 Pa. After the sputtering was completed, annealing was performed in the atmosphere at 750°C for 1 hour. By this annealing, La in the solid electrolyte was diffused to the Bi2O3 layer (La absorption layer) side, and a La-deficient LSBO was formed. Next, an operation was performed to remove the layer in which La was absorbed from this solid electrolyte. In detail, a precision polishing device was used to completely remove the Bi2O3 layer in which La was absorbed. The thickness of the La-deficient LSBO was then measured with a vernier caliper and found to be 340 μm.
[0048] Example 2 A La-deficient LSBO was produced in the same manner as in Example 1, except that the La absorption layer was annealed at 800° C. for 1 hour.
[0049] Example 3 A La-deficient LSBO was produced in the same manner as in Example 1, except that the La absorption layer was annealed at 850° C. for 1 hour.
[0050] Comparative Example 1 A solid electrolyte was produced in the same manner as in Example 1, except that the La absorption layer was not formed and therefore annealing was not performed.
[0051] [Rating 1] The solid electrolytes obtained in the examples and comparative examples were subjected to XRD measurement by the method described below. 002 / I 004 The oxide ion conductivity was measured by the method described below. The results are shown in Table 1.
[0052] [XRD measurement] Measurements were performed using a fully automated multipurpose X-ray diffractometer, SmartLab, manufactured by Rigaku Corporation, under the following conditions. Tube voltage: 40kV Tube current: 30mA X-ray source:CuKα Incident optics: Confocal mirror (CMF) Incident side slit configuration: Collimator size 1.4mm x 1.4mm Receiving slit configuration: Parallel slit analyzer 0.114deg, receiving slit 20mm Detector: Scintillation counter Measurement range: 2θ=20~60deg Step width: 0.01 deg Scan speed: 1deg / min The analysis was performed using PDXL2 from Rigaku Corporation. A straight line connecting the end points was selected for the background, and a split pseudo-Voigt function was selected for the peak shape, and the peak intensities (integral intensities) of 002 and 004 were obtained by profile fitting. As described above, the 002 and 004 peaks are c-axis oriented, and are independent peaks that do not overlap with peaks from other planes. If there is overlap with a peak from another phase, which is expected in the case of a multilayered device, the peaks can be resolved in the same way as in general XRD data analysis, so that only the peak intensities of 002 and 004 can be obtained.
[0053] [Measurement of oxide ion conductivity] Platinum films of 150 nm thickness were formed on both sides of the solid electrolyte by sputtering to form electrodes. This solid electrolyte was placed in a heating furnace, and complex impedance analysis of the solid electrolyte was performed by changing the temperature of the heating furnace. An impedance measuring device was used for the analysis, and the frequency was set to 0.1 Hz to 32 MHz. The oxide ion conductivity (S / cm) was calculated from the total resistance component (intragranular resistance + grain boundary resistance). The oxide ion conductivity at 600°C is shown in Table 1.
[0054] [Table 1]
[0055] As is clear from the results shown in Table 1, I 002 / I 004 The solid electrolytes obtained in the examples, in which the value of is within a specific range, have a conductivity about 5 times or more higher than that of the solid electrolytes of the comparative examples, and it is clear that the effect of improving the oxide ion conductivity is high.
[0056] Example 4 An intermediate layer 12 made of Bi2O3 containing yttrium was formed on both sides of the solid electrolyte obtained in Example 1. A target manufactured by the following method was used to form the intermediate layer 12. This target was used to perform sputtering on both sides of the solid electrolyte to form an intermediate layer. After the intermediate layer was formed, heating was performed at 700°C for 1 hour to manufacture a solid electrolyte joint 10.
[0057] [Target manufacturing] A given amount of Y2O3 powder and Bi2O3 powder were mixed, ethanol was added, and the mixture was mixed in a ball mill. The mixture was dried, crushed in a mortar, and fired in an alumina crucible at 700°C in air for 3 hours. Ethanol was added to the fired product, which was then crushed in a planetary ball mill to obtain a fired powder. The fired powder was placed in a 50mmφ molding machine and pressed from one direction to perform uniaxial molding, followed by hot press sintering. The sintering conditions were a nitrogen gas atmosphere, a pressure of 30MPa, a temperature of 600°C, and 3 hours. In this way, a target for sputtering was obtained.
[0058] Example 5 A target made of cerium oxide containing samarium was used instead of the target used in Example 4. This target was manufactured in the same manner as the target used in Example 4. Using this target, an intermediate layer 12 made of cerium oxide containing samarium was manufactured in the same manner as in Example 4. In this manner, a solid electrolyte joint 10 was manufactured.
[0059] Comparative Example 2 An intermediate layer made of cerium oxide containing samarium was formed on both sides of the solid electrolyte obtained in Comparative Example 1. The intermediate layer was formed in the same manner as in Example 5.
[0060] [Measurement of current density] The electrical resistance of the solid electrolyte junctions obtained in Examples 4 and 5 and Comparative Example 2 was measured. The measurement was performed at 600° C. A direct current voltage of 1 V was applied between the intermediate layers in the atmosphere, and the current density was calculated from the obtained current value. The results are shown in Table 2.
[0061] [Table 2]
[0062] As is clear from the results shown in Table 2, I 002 / I 004 It can be seen that the solid electrolyte joint in which an intermediate layer is provided on a solid electrolyte having a specific range of the value of .DELTA. is able to obtain a current density value that is about 7 times or more higher than that of the solid electrolyte joint of the comparative example. [Industrial Applicability]
[0063] According to the present invention, there is provided a solid electrolyte capable of reducing the electrical resistance of a device including the solid electrolyte, and a solid electrolyte joint having low electrical resistance.
Claims
1. The present invention is made of an apatite-type composite oxide having oxide ion conductivity, and has a peak intensity I of 004 obtained by X-ray diffraction measurement. 004 Peak intensity I of 002 002 I is the ratio of 002 / I 004 A solid electrolyte joint comprising a solid electrolyte having a value of 0.3 to 0.8 and an intermediate layer made of a metal oxide, The composite oxide is represented by the general formula: A 9.33+x [T 6.00-y M y ]O 26.0+z (In the formula, A is one or more elements selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Be, Mg, Ca, Sr, and Ba. T in the formula is an element containing Si or Ge, or both. M in the formula is Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Ga, Zr, Ta, Nb, B, and T is one or more elements selected from the group consisting of Ge, Zn, Sn, W and Mo. In the formula, x is a number from -1.33 to 1.50, y is a number from 0.40 to 2.00, and z is a number from -5.00 to 5.20, and a ratio of the number of moles of A to the number of moles of T is 1.33 to 3.
61.
2. 2. The solid electrolyte joint according to claim 1, wherein the solid electrolyte is oriented in a c-axis direction.
3. 3. The solid electrolyte joint according to claim 1, wherein the metal oxide comprises cerium oxide containing one or more elements selected from the group consisting of samarium, yttrium, gadolinium and lanthanum.
4. 3. The solid electrolyte joint according to claim 1, wherein the metal oxide is an oxide of bismuth.
5. 3. The solid electrolyte joint according to claim 1, wherein the metal oxide is a mixed conductor having oxide ion conductivity and electronic conductivity.
6. 3. The solid electrolyte joint according to claim 1, further comprising an intermediate layer, which is the same as or different from the intermediate layer, disposed on a surface of the solid electrolyte joint opposite to the surface on which the intermediate layer is disposed.
7. 3. The solid electrolyte assembly according to claim 1, which is used as an oxygen permeation element, a gas sensor, or a solid electrolyte fuel cell.
Citation Information
Patent Citations
Oxide ion conductor and its manufacturing process
JP2004244282A
Electrolyte / electrode assembly and manufacturing method therefor
JP2013051101A
Method for making isosorbide-containing polyester
JP2016094613A
Epoxy resin composition, heat conduction material precursor, b stage sheet, prepreg, heat conduction material, laminate, metal substrate and printed wiring board
JP2018021180A
Solid electrolyte and solid electrolyte bonded body
WO2019235383A1